2008
DOI: 10.1111/j.1600-0560.2007.00843.x
|View full text |Cite
|
Sign up to set email alerts
|

Plaque‐type syringoma: two cases misdiagnosed as microcystic adnexal carcinoma

Abstract: Our cases are discussed in the context of histopathologic diagnosis. Detailed histopathologic findings of syringoma, as well as other considerations in the differential diagnosis, are reviewed. We also include a review of all cases of plaque-type syringoma published to date.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
34
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 17 publications
3
34
0
Order By: Relevance
“…Histopathologically, the deep and plaque types can be mistaken for microcystic adnexal carcinoma. 68,69 We did not identify any unusual variants of syringoma, such as giant, plaque-like, or clear cell variants.…”
mentioning
confidence: 99%
“…Histopathologically, the deep and plaque types can be mistaken for microcystic adnexal carcinoma. 68,69 We did not identify any unusual variants of syringoma, such as giant, plaque-like, or clear cell variants.…”
mentioning
confidence: 99%
“…There are no accepted differences in immunohistochemical profile between syringoma and MAC/SC, further emphasizing the need for optimal biopsy specimens. This difficulty has recently been highlighted by Suwattee et al, 33 who reported 2 cases of plaquetype syringoma initially misdiagnosed as MAC. In our patients, the combination of the clinical presentation and classic histological features on adequate biopsy specimens aids in accurate diagnosis and highlights the unique clinicopathological features of this rare manifestation of syringoma.…”
Section: Discussionmentioning
confidence: 96%
“…MAC typically occurs on the head and neck, particularly the central face, in middle‐aged patients and presents as an indurated single plaque. Plaque‐like syringomas can be misdiagnosed histologically as MAC 5 . It is therefore important to obtain an adequate biopsy specimen, as differentiating between the two diagnoses can be difficult, particularly with superficial biopsies when infiltrative growth patterns and perineural extension cannot be accurately assessed.…”
Section: Discussionmentioning
confidence: 99%